Flexible BaTiO3/SiC@PbTiO3/epoxy composite films with enhanced dielectric performance at high frequency. Issue 14 (15th July 2022) - Xu, Pengpeng; Yu, Junyi; Li, Chaofan; Luo, Suibin; Ke, Shanming; Zhou, Yangbo; Yu, Shuhui; Sun, Rong
Abstract: Flexible polymer composites with high dielectric constants and low dielectric losses at high frequencies are highly desired in microwave and RF applications. However, a high dielectric constant is often obtained at the expense of flexibility because a high loading of filler is needed. In this work, we synthesize a core-shell structured 1D filler by coating high-dielectric-constant PbTiO3 onto the surface of low-thermal-expansion-coefficient SiC nanofibers, which are then incorporated into the epoxy matrix together with BaTiO3 nanoparticles to form the multi-phase BaTiO3 /SiC@PbTiO3 /epoxy composite film. A high dielectric constant (35 at 100 Hz and 20 at 5 GHz) and a low dielectric loss (0.023 at 100 Hz and 0.13 at 5 GHz) are achieved as the filling content of SiC@PbTiO3 and BaTiO3 is 5.24 wt% and 80 wt%, respectively. Prediction models of the effective dielectric constant of polymer-based composites reveal that a continuous polarization network is constructed in the composites owing to the physical contact between BaTiO3 and PbTiO3 . The construction of the multi-phase filler provides a feasible way to effectively adjust and improve the dielectric properties of polymer-based composite films.